Silver-coated metallic and dielectric magnetic nanospheres: Localized surface plasmons and circular dichroism - P. Varytis; N. Stefanou (Optics Communications, 2016)
A thorough study of localized surface plasmons and associated strong circular dichroism, which can occur in silver-coated metallic and dielectric magnetic nanospheres, is reported by means of both quasistatic and full electrodynamic calculations taking into account the actual (magneto) optical response of the constituent materials, including dispersion and losses. It is shown that such composite magnetoplasmonic nanoparticles offer a versatile platform for engineering hybrid plasmon modes that give rise to sharp absorption resonances and subject to large magneto-optic splitting, leading to giant magnetic circular dichroism signals, by properly choosing the different materials and tuning the geometrical parameters involved.